CONCEPTUAL BASIS OF PROFESSIONALLY ORIENTED FOREIGN LANGUAGE TRAINING OF FUTURE SPECIALISTS IN APPLIED MECHANICS - Alla Feschuk (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2016)
The article deals with the problem of definition of the notion of "professionally oriented foreign language training of future specialists in applied mechanics", particularly, it reveals the differentiation of the notions  of "foreign language training", "foreign language education" and "teaching foreign languages", determines the purpose and the content of foreign language education and teaching foreign languages and the peculiarities of foreign language education of future specialists in applied mechanics. Integration into European educational space caused the changes in the Ukrainian educational market including professional training of future specialists in applied mechanics who should be able to adapt to multicultural, multilingual environment for the realization of personal and professional needs. The concept of professionally oriented foreign language training is analyzed and defined by scientists as a process of teaching foreign languages oriented to the formation of foreign language professional competence for solving professional tasks in their sphere. The key factors of professionally oriented foreign language training of future specialists in applied mechanics (cognitive and informational, linguistic, professional, psycholinguistic, content and structural) are introduced in the paper. The leading role of foreign language education consists in effective communication, cultural awareness, ability to work and adapt to multilingual and multicultural teams and high level of communication competence, which are considered as the key requirements of the recruitment strategies of employers.